THE IMPACT OF DANCE ON THE DEVELOPMENT OF COPING MECHANISMS FOR NARCOLEPSY: A NARRATIVE ANALYSIS - Zaini, Mimi Fitriana; Manesh, Niloufar Heshmati (Jurnal Ilmiah Peuradeun, 2020)
The purpose of this study was to highlight the experiences of dance as an approach to give optimism in reducing the difficulties of narcoleptic patients that stem close to normal social functioning, and to explore the consequences of dance on narcoleptic patients in physiological, environmental and interpersonal aspects. A semi-structured interview was conducted to 3 selected narcoleptics, age ranging from 30 to 45 years, with at least 6 months of dance experience, using a purposive sampling procedure. Thematic analysis enabled the identification of key components of the impacts of dance and its coping mechanisms as the generated themes from the two research questions to include; 1) Dance as a form of Expression, Being Mindful, Decreased Symptoms, Self-achievement, Self-Enjoyment, Satisfaction level, Self-contentment, Stress-release and Balance of health, 2) Flexibility in Dance Style, Wider perspective in Dance Style, Social Functioning, Attention Skills, Emotion Management, Positive mind-set, Time management, and Intra-Familial relation. The finding from the two research questions was identified across the generated themes. The findings were expected to increase awareness among people in the issue of narcolepsy and its consequences for the purpose of mental health and well-being to promote a healthy lifestyle and better quality of life. Research Implications for the improvement of narcoleptics were also discussed for the purpose of module developments and interventions.